(untitled) (Conferencea, 2024)
The actuality. Diabetic foot syndrome is one of the terrible complications of diabetes mellitus. In 55% of cases, this complication occurs in patients aged 25 to 75 years. To implement the basic principles of modern personalized medicine, it is relevant to study the genetic aspect of multifactorial diseases, which include diabetes mellitus and its complications, in order to identify numerous genetic polymorphisms that should be taken into account in combination with modifiable and non-modifiable non-genetic factors.